West Antarctic ice retreat and paleoceanography in the Amundsen Sea in the warm early Pliocene - Passchier, Sandra; Hillenbrand, Claus-Dieter; Hemming, Sidney; Ehrmann, Werner; Frederichs, Thomas; Bohaty, Steven M.; Leon, Ronald; Libman-Roshal, Olga; Mino-Moreira, Lisbeth; Gohl, Karsten; Wellner, Julia (Nature Communications, 2025)
Mass loss from polar ice sheets is poorly constrained in estimates of future global sea-level rise. Today, the marine-based West Antarctic Ice Sheet is losing mass at an accelerating rate, most notably in the Thwaites and Pine Island glacier drainage basins. Early Pliocene surface temperatures were about 4 °C warmer than preindustrial and maximum sea level stood ~20 m above present. Using data from a sediment archive on the Amundsen Sea continental rise, we investigate the impact of prolonged Pliocene ocean warmth on the ice-sheet−ocean system. We show that, in contrast to today, during peak ocean warming ~4.6 − 4.5 Ma, terrigenous muds accumulated rapidly under a weak bottom current regime after spill-over of dense shelf water with high suspended load down to the rise. From sediment provenance data we infer major retreat of the Thwaites Glacier system at ~4.4 Ma several hundreds of km inland from its present grounding line position, highlighting the potential for major Earth System changes under prolonged future warming.